Antecedents and Outcomes of Corporate Reputation Customer-based Analysis - MUHAMMAD TUFAIL; AMIR ISHAQUE; MUHAMMAD IRFAN (Journal of Business & Tourism, 2021)
For any organization its image and reputation is the level of affectionateness in the minds of employees, customers, expected candidates, and competitors, Reputation is the most critical and strategic asset that a corporation possess (Cravens et al., 2003). The objectives of the study was to examine the antecedents and outcomes of corporate reputation. The study was quantitative in nature. Data were collected by using convenient sampling technique from twin cities (i.e. Islamabad and Rawalpindi) of Pakistan. Respondents were asked to answer the questions keeping in mind the mobile company whose connection they use frequently or on permanent basis. Simple correlation and regression methods were used for analysis of data. Results revealed that if a customer is satisfied with the products and services offered by the company than the reputation of the company in the eyes of the customer will increase. In the same way, when customer has trust on the services offered by the company his confidence level will increase on the future offers and service quality of company resulting an increase in the reputation of the firm and this company reputation will influence customer loyalty and positive word of mouth. Managerial implications and recommendations for future research are given at the end.